(untitled) (Historia, 2021)
Benjamin Norden and the Neptune events, 1848-1850 Who Benjamin Norden actually was, and the role he played in the development of the South African way of life may probably never be fully known. This article outlines the life of Norden as an 1820 settler in the eastern Cape and later as an active member of the developing Jewish community in South Africa. It focusses specifically on his involvement as a leader of Cape Town society in the Anti-Convict Association and the Neptune incident. Norden’s concern about ethical values were interpreted as being against the norms of the Anti-Convict Association whereafter he was not only shunned by society in general, but also by the Jewish community.